(untitled) (Journal of Economic Research & Business Administration, 2018)
The modern world lives in conditions of acute social problems. Therefore, new effective tools for managing sustainable development are especially important today. As an approved effective tool for sustainable development of the company, the concept of corporate social responsibility has spread throughout the world. Understanding by business leaders of their special, leading role in this work led to the emergence of the term «corporate social responsibility» at the end of the 20th century, which became the most important component of the notion of sustainable development not only of business but of humanity as a whole. The experience of the highly developed countries of the world clearly demonstrates that social problems are not solved only by the state. The commercial sector should also be actively involved in this process, since the well-being of society, stability and competitiveness of a country depend on the responsibility of each member, each civil institution. The main prerequisite for such cooperation is to rely on a socially responsible business. Today, thanks to the actions or, rather, the awareness of entrepreneurship of their role and place in solving state tasks, the terms «socially responsible», «socially oriented» from some virtual model are gradually becoming a reality. Elements of socially responsible entrepreneurship are taking root in the business culture of many Kazakhstani companies. Companies and entrepreneurs create new jobs, do charity work, and do concrete work to develop the social and cultural infrastructure of the city and village.